A membership categorization analysis of roles, activities and relationships in inclusive research conducted by co‐researchers with intellectual disabilities. Issue 3 (22nd February 2019) - Frankena, Tessa K.; Naaldenberg, Jenneken; Tobi, Hilde; van der Cruijsen, Anneke; Jansen, Henk; van Schrojenstein Lantman ‐ de Valk, Henny; Leusink, Geraline; Cardol, Mieke
Abstract: Background: Inclusive research is studied mainly in short‐term collaborations between researchers with and without intellectual disabilities focusing on practicalities. Structural study of long‐term collaborations can provide insight into different roles of inclusive researchers, thereby contributing to a collective approach. Method: Interviews with inclusive research team members ( n = 3), colleagues ( n = 8), and managers ( n = 2) and three group discussions within the inclusive research team were held. Data were analysed following membership categorization analysis (MCA) adapted to the needs of the inclusive research team. Results: This MCA provides insight into the complexity of inclusive research, reflected in the multitude of identified roles and activities. Analysis indicates that researchers with and without intellectual disabilities complement each other. Conclusions: The activities identified in this study provide valuable information for discussing roles and responsibilities from the outset, so that dialogue starts at the core of inclusive research: the process between researchers with and without intellectual disabilities.